Vaccine nationalism will persist: global public goods need effective engagement of global citizens - Stuart J. Peacock (BMC, 2022)
Abstract Covid-19 presents a unique opportunity to transform democratic engagement in the governance of global public goods. In this paper, I describe a global public goods framework and how it relates to Covid-19 vaccines, and summarize some of the global responses to Covid-19. I discuss some of the global threats to health and prosperity posed by the inequitable distribution of vaccines, and propose transformative thinking to democratically engage citizens in the governance of global public goods. In recent years, public-private partnerships and philanthropic organizations have successfully stepped in to help international organizations like the UN and WHO provide global public goods, but they are not democratically elected or publicly accountable. Global public goods are critical to addressing Covid-19, future pandemic preparedness, global health policy, health equity, and the unfolding climate crisis. To make us more resistant and resilient to future global health crises we need transformative thinking to democratically engage global citizens. We need to lay the foundations for a 'global social contract' on global public goods.